RANCANG BANGUN FRAMEWORK SISTEM INFORMASI KASIR BERBASIS WEB UNTUK MENDUKUNG DIGITALISASI UMKM: Point of Sales, Information Systems, MSMEs, Waterfall, Web - Yudistira, Miranty; Setiya Ningsih, Ari; Lutvianita, Febby; Andrianti, Ari; Bima Alfajri, Willy (JURNAL AKADEMIKA, 2025)
MSMEs play an important role in the Indonesian economy because they are able to absorb labor, strengthen the real sector, and market local products to a wider market. One example is the Pempek Madam MSME in Jambi, which is engaged in the production and sale of pempek as a regional specialty food. This study aims to develop a web-based cashier information system framework that not only improves transaction management efficiency at Pempek Madam but can also be adapted for other MSMEs with similar business models. The development was carried out using the Waterfall method, starting from needs analysis to implementation, with the user interface design created using Figma. The design includes a login page, main menu, product categories, transaction process, payment methods, sales reports, and profile settings. System testing was conducted through black box testing and User Acceptance Test (UAT) to ensure functionality and ease of use. The test results showed that all features worked well, the interface was easy to understand, and the workflow was in line with user expectations. This framework is considered capable of improving the operational efficiency of MSMEs and is ready to be replicated for various similar types of businesses, supporting the acceleration of MSME digitalization in Indonesia.